The Role of the Central Java Provincial Wage Council in Determining Minimum Wages in the Central Java Province Region: Peran Dewan Pengupahan Provinsi Jawa Tengah dalam Penetapan Upah Minimum di Wilayah Provinsi Jawa Tengah - Figur Rakasiwi (Universitas Negeri Semarang, 2012)
Manpower development should be organized in such a way, so that the rights and protections for workers' fundamental fulfilled, and at the same time can create conditions conducive to the development of the business. But the reality is not so, a lot going on demos workers demanding higher minimum wage, in this case the need for the role of provincial councils to provide a solution. The authors are interested in examining the role of councils in the province of minimum wage in the province of Central Java. This study aims to determine the extent to which a given role Wage Council to the Governor of Central Java province in setting the minimum wage by legislation. This study uses a qualitative approach, empirical and juridical validity of the data using triangulation techniques. The results showed that the role of provincial councils covering from January to November, which are included in the monthly activities such as surveys KHL January to September, October to December to predict the value of the KHL in a way y.o.y (year on year), and then after that make the formula calculation taking into account the value of MSE khl, labor market conditions, productivity, and marginal businesses. Given the role of provincial councils are in accordance with the legislation, only provincial councils still have constraints, and attempts to overcome that: difficult to agree when the plenary meeting, the efforts made by the councils is to persuasive approach, making the secretariat, create small groups; many districts / cities late in delivery KHL survey, efforts Wage Council is to send an official letter; KHL survey data is not realistic with fairness KHL field and there is a component that does not comply with the conditions of the district/ city, then solve it by providing records and asked to confirm again, for KHL components that do not fit the chosen components KHL are often consumed by the public; too much of the formula calculation and prediction city minimum wage KHL, attempt to resolve it by way of implementing the plenary meeting in order to get the type of the formula required. Suggestions for provincial councils are able to remove the personal ideologies and groups, so that the task can be executed better.